Femininity within the context of Kurdish nationalist discourse in the late nineteenth and earrly twentieth centuries - Karaman, Emine Rezzan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This thesis discusses femininity within the context of Kurdish nationalist discourse developed in the late Ottoman and early Republican period. A significant part of the study concentrates on the analysis of four Kurdish-Ottoman publications (Kurdistan, Jîn, Hetaw-i Kurd, Roj-i Kurd); each being representative of contradictory political stances and displaying the fragmented nature of the Kurdish intelligentsia who played an important role in the center-periphery relationship. My objective is, firstly, to deconstruct the meta-narratives imposed by traditional historical understanding by looking at history from below, by looking at the center from the periphery, from the perspective of a marginalized community which was deprived of being the subject of history and left in the shadows; and secondly, to adopt an approach which calls us to see the relationship between power and representation and accordingly, how those who hold power became the main historical actors while those deprived of power were turned into objects without a history to speak of. With the same motivation, the thesis also examines how the Western/non-Western societies put the other(s) under erasure when they constructed concepts like nationalism, feminism or human rights; how the West assumed its constructions as “universal” and the critiques raised against this assumption from different parts of “the Third World”, particularly India; how the Kurds who lost their autonomy exteriorized the state and its discourses to make comparisons, putting a distance between themselves and Armenians, Turks, Arabs and Greeks; how different and peculiar the Kurdish nationalist discourse was from the Western-oriented “universal” nationalisms; and how the active/passive roles taken by Kurdish women as “the symbols of the nation and modernization” were developed.
Keywords: Women, Kurdish.; Feminism -- Turkey.; Kurds -- Turkey.